2020
DOI: 10.1051/bioconf/20202100007
|View full text |Cite
|
Sign up to set email alerts
|

Trophic connections of the brown marmorated stink bug Halyomorpha halys Stål in the conditions of the invasive area on the Black Sea coast of the Caucasus

Abstract: Brown marmorated stink bug Halyomorpha halys (Stål, 1855) is a highly aggressive crop pest that has appeared in Russia since 2014. Under the conditions of a new invasive species area, it is important to study the characteristics of the pest biology, including the study of the range of trophic plants. The studies were carried out in the zone of humid subtropics of the Black Sea coast of the Caucasus in 2014-2019. The study of trophic connections was carried out in the course of regular surveys of the region’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Analysis of the obtained data and literature sources (the most complete summary of the trophic relationships of H . halys in Russia is given by Borisov et al, 2019 and Zakharchenko et al, 2020), showed that the field maple ( Acer campestre L.), green ash ( Fraxinus pennsylvanica Marshall) (Figure 3), London plane ( Platanus × hispanica Münchhausen), Persian walnut ( Juglans regia L.) (Figure 1) and Oregon grape ( Berberis aquifolium Pursh) (Figure 6) have been recorded as the host plants of H . halys for the first time in Russia.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Analysis of the obtained data and literature sources (the most complete summary of the trophic relationships of H . halys in Russia is given by Borisov et al, 2019 and Zakharchenko et al, 2020), showed that the field maple ( Acer campestre L.), green ash ( Fraxinus pennsylvanica Marshall) (Figure 3), London plane ( Platanus × hispanica Münchhausen), Persian walnut ( Juglans regia L.) (Figure 1) and Oregon grape ( Berberis aquifolium Pursh) (Figure 6) have been recorded as the host plants of H . halys for the first time in Russia.…”
Section: Resultsmentioning
confidence: 94%
“…Both adults and first-to fifth-instar larvae of H. halys were found to have fed on fruits and leaves of a wide range of ornamentals (12 plant species from eight plant families) (Figures 2,3,6) but only on four fruit crops (four plant species from four plant families) (Figures 1,4,5). Analysis of the obtained data and literature sources (the most complete summary of the trophic relationships of H. halys in Russia is given by Borisov et al, 2019 andZakharchenko et al, 2020), showed that the field maple (Acer campestre L.), green ash (Fraxinus pennsylvanica Marshall) (Figure 3), London plane (Platanus × hispanica Münchhausen), Persian walnut (Juglans regia L.) (Figure 1) and Oregon grape (Berberis aquifolium Pursh) (Figure 6) have been recorded as the host plants of H. halys for the first time in Russia. The highest abundance of H. halys was recorded on common catalpa (Catalpa bignonioides Walter), Oregon grape (Berberis aquifolium Pursh), Judas tree (Cercis siliquastrum L.), green ash (Fraxinus pennsylvanica Marshall), plane maple (Acer pseudoplatanus L.), field maple (A. campestre L.) and Chinese sumach (Ailanthus altissima (Miller) Swingle) (Table 1).…”
Section: R E Su Lt S a N D Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In different parts of its invasive range, this polyphagous pentatomid demonstrates tendencies to expand its' host plant range (D. Lupi et al, 2017; M.-A. Aghaee et al, 2018; S. Francati et al, 2021; V Zakharchenko et al, 2020)…”
mentioning
confidence: 99%